(NwYSOKOTEMPERATURNYE SWERHPROWODNIKI (B:s (NpER(B. (NS ANGL(B. /s - (NsLEJT(B, (NaRTUR u(B.s; (NmESSMER(B, (Nr(B.(Np(B.s; (Nm\RFI(B, (Nr(B.(Nb(B.s; (NnELSON(B, (Nd\WID l(B.s; (NdVORDV(B, (Nt(B.s ((NmOSKWA (B:s (NmIR (B,s, 1988)
(NbIBLIOGR(B. (NW KONCE GLAWs
Keywords: (NsWERHPROWODNIKI WYSOKOTEMPERATURNYEs